The Role of Language in the Organizational Socialization Process : The Newcomer’s Perspective - Saarinen, Kira (My University, 2021)
Individuals are crossing both organizational and national boundaries more than ever before. Therefore, today’s organizational environment is increasingly multilingual and new employees are constantly adjusting to their new organizations, teams, and jobs in a second language. Although many companies opt for English as the common company language to ease communication, barriers remain, and language issues can arise from proficiency in the common company language in addition to the other languages present within the organization. As organizational socialization is the primary process through which new employees transition from outsiders to effective insiders and can be a com-petitive advantage, it is crucial to understand the effects of language on the process. The aim of this thesis was to understand how language affects the socialization ex-periences of new employees who speak a different native language than the majority work group. To gain an understanding of newcomer experiences the study was conduct-ed as a qualitative interview study. The empiric study consists of nine semi-structured interviews with non-Finnish employees working in a predominantly Finnish-speaking environment at a Finnish multinational company. The results of the study indicate that language makes the adjustment process of newcomers who do not share a first language with the majority work group more diffi-cult. Language was found to hinder social integration and knowledge sharing. Mean-while, newcomer proactivity, newcomer empathy, social support and organizational socialization tactics were found to be supporting elements in the process. In addition, language-related issues did not seem to significantly affect socialization outcomes.

Nykypäivän työympäristö on kansainvälisempi kuin koskaan ennen. Työntekijöiden ylittäessä kansallisia- sekä organisatorisia rajoja kielen merkitys työpaikalla korostuu. Vaikka englannin kieltä käytetään organisaatioissa usein yhteisenä kielenä se ei poista haasteita joita esiintyy kun kommunikoidaan vieraalla kielellä. Lisäksi, vaikka työpaikan virallinen kieli olisikin englanti, työntekijöiden käyttämiä kieliä voi olla useita. Uuden työntekijän sosialisaatio on olennainen prosessi jonka kautta hän sopeutuu uuteen työhönsä ja työympäristöönsä. Onnistuneesta sosialisaatioprosessista voi olla hyötyjä sekä yksilölle että organisaatiolle, joten on tärkeää ymmärtää miten kieli vaikuttaa tähän prosessiin. Tämän tutkielman tarkoituksena oli ymmärtää, miten kieli vaikuttaa uusien työntekijöiden sosiaalistumiskokemuksiin, jotka puhuvat eri äidinkieltä kuin enemmistöryhmä. Tutkimus tehtiin laadullisena haastattelututkimuksena, jotta saataisiin paras käsitys uusien työntekijöiden kokemuksista. Empiirinen tutkimus koostuu yhdeksästä , semi-strukturoidusta haastattelusta ei-suomenkielisten työntekijöiden kanssa, jotka työskentelevät pääasiassa suomenkielisessä ympäristössä suomalaisessa monikansallisessa yrityksessä. Tutkimuksen tulokset osoittivat, että kieleen liittyvät haasteet voivat vaikeuttaa uusien työntekijöiden sopeutumista. Kielen havaittiin vaikeuttavan sosiaalista integraatiota ja tiedon jakamista. Uusen työntekijöiden proaktiivisuuden ja empatian sekä muilta saadun tuen ja organisaation perehdytyksen havaittiin tukevan sosialisaatioprosessia. Lisäksi kieleen liittyvät haasteet eivät näyttäneet vaikuttavan merkittävästi sosiaalistumistuloksiin.
Keywords: organizational socialization, socialization, onboarding, language,